Childhood practice and play as determinants of adolescent intrinsic and extrinsic motivation among elite youth athletes - Thomas, A.; Güllich, A. (European Journal of Sport Science, 2019)
The study empirically tested the postulate of the Developmental Model of Sport Participation (DMSP; Côté, J., Baker, J., & Abernethy, B. (2007). Practice and play in the development of sport expertise. In R. Eklund & G. Tenenbaum (Eds.), Handbook of sport psychology (pp. 184-202). Hoboken, NJ: Wiley) that diversified childhood self-led sport play will beneficially affect future, adolescent intrinsic motivation. Participants were 178 elite youth athletes (age 15.3 ± 1.5 years) from several game and non-game sports; 117 were members of the federal state or national junior squad in their respective sport. A questionnaire measured current (adolescent) intrinsic and extrinsic motivation of the youth athletes using the Sport Motivation Scale (Pelletier, L. G., Fortier, M. S., Vallerand, R. J., Tuson, K. M., Brière, N. M., & Blais, M. R. (1995). Towards a new measure of intrinsic motivation, extrinsic motivation, and amotivation in sports: The sport motivation scale (SMS). Journal of Sport & Exercise Psychology, 17, 35-53) and their earlier volume of childhood engagement (through 12 years) in coach-led practice and self-led play in their respective main sport and other sports. Analyses revealed that adolescent intrinsic motivation was not significantly correlated with earlier childhood self-led sport activities, self-led play in particular, or childhood sports diversification. Furthermore, considering all different types of childhood sport activities together in multiple regression analyses, they did not provide meaningful explanatory power regarding adolescent intrinsic or extrinsic motivation. In summary, the results did not provide support for the postulate of the DMSP among elite youth athletes. The findings suggest that future research may seek to enable more robust empirical substantiation of the DMSP postulate.